Thermal Efficiency in Steel Reheating Process (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this study, the energy consumption by theprocess of steel billet reheating in an industrial steel reheatfurnace at the Libya Iron and Steel Company (LISCO) isconsidered. It is known that in the steel industry, one of the processes requiring the most energy is the process ofreheating the steel prior to hot rolling. A comprehensivemass and heat balance was performed on the furnace, takinginto account all actual entering and exiting furnaceparameters. Furnace thermal efficiency was found to be lowand heat losses from different areas of the furnace wereconsiderable.